ANALISIS KETERAMPILAN BERBICARA MELALUI PENGGUNAAN BUKU CERITA BERGAMBAR PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV DI SDN BELENDUNG KOTA TANGERANG - Hidayati, Nurul; Septy Nurfadhillah; Asih Rosnaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe speaking skills through the use of picture storybooks in Indonesian language subjects for class IV students at Belendung Elementary School, Tangerang City. This research is qualitative research with subjects of 9 students in class IV and class IV teachers. The techniques used to collect data are observation, interviews with fourth grade teachers and students, tests, documentation and data analysis which is carried out by reducing data, presenting data and drawing conclusions. So it can be concluded that this research shows that speaking skills through the use of picture story books in class IV students are quite good, on the 5 indicators assessed, namely; pronunciation, intonation, fluency, expression, and accuracy.